2017
DOI: 10.17265/2161-6213/2017.7-8.001
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Leachability of Coal Fly Ashes from Different Types of Coal Fired Power Plants

Abstract: Abstract:The leaching behavior of arsenic (As) in coal fly ash collected from two different types of coal fired power plants (unit 1 and unit 2: 600 MWe) has been investigated to understand their behavior during combustion and effect of different boiler types on arsenic leachability. To determine dominant factors on arsenic leaching from coal fly ash, the change of arsenic chemical during coal combustion was predicted from the perspective of thermodynamic equilibrium and leaching test under alkaline condition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Hayashi [8] studied the chemical state of boron in coal fly ash and concluded that boron associated with calcium and magnesium is difficult to leach. Wang [9] stated that As and Se have a high mobility in alkaline pH, and Sri et al [10,11] stated that leaching of arsenic is related to calcium oxide content in coal fly ash.…”
Section: Introductionmentioning
confidence: 99%
“…Hayashi [8] studied the chemical state of boron in coal fly ash and concluded that boron associated with calcium and magnesium is difficult to leach. Wang [9] stated that As and Se have a high mobility in alkaline pH, and Sri et al [10,11] stated that leaching of arsenic is related to calcium oxide content in coal fly ash.…”
Section: Introductionmentioning
confidence: 99%
“…The leaching of As and Se from acidic ashes could be described by sorption of iron oxide, while the leaching from the alkaline ashes appeared to be controlled by sorption in the alkaline calcium phase [20,23]. The presence of Ca in fly ash plays an important role in the leaching behavior of As, B, and Se, in which the leaching of As, B, and Se may involve the trapping of As, B, and Se species by the ettringite phase (3CaO·Al 2 O 3 ·3CaSO 4 ·32H 2 O), leading to a decrease in leaching under alkaline conditions [18,19,[24][25][26][27][28]. Therefore, Ca content and the sorption process are known to play important roles in the release of As, B, and Se from CFA.…”
Section: Introductionmentioning
confidence: 99%